2021
DOI: 10.5937/jomb0-30424
|View full text |Cite
|
Sign up to set email alerts
|

Associations of galectin-3 expression and LGALS-3 (rs4652) gene variant with coronary artery disease risk in diabetics

Abstract: Background Galectin‑3 protein that is encoded by lectin galactoside-binding soluble-3 (LGALS-3) gene serves as an important genetic factor in type 2 diabetes mellitus (T2DM) and its cardiovascular obstacles in various populations. We aimed to elicit the pro-inflammatory effect of galectin-3 as determined by interleukin-6 (IL-6) serum levels and to explore the relationship between galectin-3 (LGALS-3 rs4652) gene variation and its expression levels with coronary artery disease (CAD) risk among T2DM Egypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…One of the studies conducted by Zhen et al (7), reported elevated expression of Galectin-3BP and positive correlation with obesity and MetS in 932 Chinese adolescents. On the other side Besma et al (21) obtained no statistically significant results regarding BMI among patients with type 2 diabetes mellitus regarding rs4644 genotype. One of the possible explanation of these results are differences in gonadal hormonal status.…”
Section: Discussionmentioning
confidence: 90%
“…One of the studies conducted by Zhen et al (7), reported elevated expression of Galectin-3BP and positive correlation with obesity and MetS in 932 Chinese adolescents. On the other side Besma et al (21) obtained no statistically significant results regarding BMI among patients with type 2 diabetes mellitus regarding rs4644 genotype. One of the possible explanation of these results are differences in gonadal hormonal status.…”
Section: Discussionmentioning
confidence: 90%
“…Inflammation and local innate immune response are considered cornerstone pathogenic mechanisms of atherosclerotic CAD (13) . Ibrahim et al (14) concluded that Gal-3 expression level was a CAD risk factors in diabetic patients. Our aim was to assess serum Gal-3 levels among CAD cases and its role in the evaluation of CAD severity and prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that altered expression of DDX58 [413], STAT1 [414], TLR4 [415], CYP2D6 [416], JAK2 [417], TLR2 [418], DUSP6 [419], HDAC9 [420], LATS2 [421], CA2 [150], HIPK3 [422], CCR2 [423], GAB1 [120], UFL1 [424], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [425], PRKAR1A [265], SIRT1 [426], FGL2 [427], TET2 [428], ASCC2 [429], BIN1 [430], HSPB1 [431], IGFBP4 [432], TRPM4 [433] and LGALS3 [434] might be associated with the progression of heart failure. STAT1 [435], TLR4 [436], ABCA1 [437], PTGS2 [68], CYP2D6 [438], CR1 [439], PDK4 [440], RNF213 [441], ZDHHC17 [70], TLR8 [442], PDGFC (platelet derived growth factor C) [443], TLR2 [444], CYP1B1 [445], HDAC9 [446], IL1RN [447], GCH1 [448], EGR1 [449], ZEB2 [450], PLA2G7 [451], CCR2 [452], GCLC (glutamate-cysteine ligase catalytic subunit) [258], VEGFA (vascular endothelial growth factor A) [453], CD46 [454], NFKBIZ (NFKB inhibitor zeta) [455], LDLR (low density lipoprotein receptor) [456], TLR6 [457], SIRT1 [458], NOD2 [459], FGL2 [460], IDH1 [461], TET2 [462], PFKFB2 [463], KDM6A [464], IKZF2 [465], ZNF606 [466], PF4 [467], CCR7 [468], RUNX3 [469], TCF7 [470], PPBP (pro-platelet basic protein) [471], IGFBP4 [280], HSPG2 [472] and LGALS3 [236] expression might be regarded as an indicator of susceptibility to CAD. STAT1 [473], TLR4 [367], JAK2 [474], PDGFC (platelet derived growth factor C) […”
Section: Discussionmentioning
confidence: 99%